The Policy Ministry of Health Make Changes Health System Law, Based on Timor-Leste Law. Nu 10/2004 - Da Cruz, Leontino (International Scientific Journal of UNPAZ Timor-Leste, 2026)
This research examines the persistent gap between national health governance frameworks, established by Law No. 10/2004, and their on-ground implementation. It investigates how regulatory fragmentation, weak coordination, and bureaucratic resistance impede effective enforcement of health standards. The study aims to identify root causes of implementation failures by analyzing policy direction and legislative accountability within the Ministry of Health, ultimately seeking to align legislative principles with practical enforcement for improved public health outcomes. The enactment of Law No. 10/2004 serves as a foundational pillar for national health governance, yet persistent discrepancies between regulatory frameworks and on-ground implementation have hindered the optimization of public health services. Despite this legislative foundation, challenges such as regulatory fragmentation, weak inter-agency coordination, and bureaucratic resistance continue to impede the effective enforcement of national health administrative standards. Consequently, this research aims to identify the root causes of these implementation failures by evaluating the political direction of health policies and their alignment with national. Furthermore, this investigation emphasizes the urgency of assessing legislative accountability within the Ministry, given that legislative gaps often lead to suboptimal healthcare management and governance. By synthesizing these legal challenges, this study addresses the critical need to align legislative principles with practical enforcement, ensuring that administrative procedures remain consistent with the broader national interest. This evaluation is particularly vital as recent legislative shifts in the health sector have faced persistent criticism regarding the lack of deliberative inclusiveness and the potential erosion of oversight mechanisms. addressing these vulnerabilities is essential to mitigate the risks associated with jurisdictional conflicts and the marginalization of independent professional bodies. To achieve this, the analysis shifts focus toward the mechanisms governing the policy cycle, where the transition from legislative formulation to operational implementation remains a persistent hurdle for sustainable health administration. By utilizing the ROCCIPI framework, this study dissects the interplay between legal mandates and institutional behavior to determine why the Ministry of Health often faces difficulties in translating codified provisions into consistent public health outcomes. By identifying these systemic impediments, the study clarifies how the constitutional state responsibility to fulfill health rights is frequently compromised by operational and coordination failures.
Keywords: Law No. 10/2004; Legislative accountability; National health governance; Health policy; Jurisdictional conflicts; Oversight mechanisms; Deliberative inclusiveness; Practical enforcement